An analysis of Ziauddin Sardar's approach to integration of knowledge = Analisis pendekatan Ziauddin Sardar terhadap integrasi ilmu - Uddin, Md Helel; Ushama, Thameem (IIUM Press, 2024)
This paper analyses Ziauddin Sardar's (b. 1951) approach to integrating knowledge. He is a prominent British-Pakistani Muslim scholar. He is a polymath writer, cultural critic, broadcaster, futurist, internationally renowned scholar and public intellectual. He is the author of over 50 books. Sardar's main concern is that the world is changing rapidly with the advancement of technology. People are getting closer to each other irrespective of religion, caste, civilisation, culture, and race. The knowledge production and process cannot be used to dominate a particular civilisation. Hence, a holistic, diverse, integrated, and universal approach is needed. Integration of Knowledge is the most appropriate term for this changing world. This study employs a descriptive and analytical approach for gathering and examining data. This research has primarily relied on library research, utilising books, papers, and online databases. The research findings are anticipated to enhance the understanding of Sardar's method of knowledge integration among students, teachers, and academics.